2022
DOI: 10.3390/v14030548
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Species of Trichomonasvirus in the Human Parasite Trichomonas vaginalis Using Transcriptome Mining

Abstract: Trichomonas vaginalis is the most common non-viral cause of sexually transmitted infections globally. Infection by this protozoan parasite results in the clinical syndrome trichomoniasis, which manifests as an inflammatory disease with acute and chronic consequences. Half or more isolates of this parasite are themselves infected with one or more dsRNA viruses that can exacerbate the inflammatory syndrome. At least four distinct viruses have been identified in T. vaginalis to date, constituting species Trichomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Based on phylogenetic distinctions, at least 4 major TVV species have been identified in the Trichomonasvirus strain, with TVV1 being closer to TVV2 and TVV3 than to TVV4 ( 15 ). The fifth species belonging to the Trichomonasvirus strain was named TVV5 and was recently characterized by a novel sequence assembly and classification; TVV5 shows low sequence identity with the other 4 species ( 16 ).…”
Section: Discovery Of Parasitic Protozoan Virusesmentioning
confidence: 99%
“…Based on phylogenetic distinctions, at least 4 major TVV species have been identified in the Trichomonasvirus strain, with TVV1 being closer to TVV2 and TVV3 than to TVV4 ( 15 ). The fifth species belonging to the Trichomonasvirus strain was named TVV5 and was recently characterized by a novel sequence assembly and classification; TVV5 shows low sequence identity with the other 4 species ( 16 ).…”
Section: Discovery Of Parasitic Protozoan Virusesmentioning
confidence: 99%
“…reported the presence of a novel TVV, namely TVV5. 44 T. vaginalis can harbour one or more types of TVVs. 2 The prevalence of TVV varies in different clinical T. vaginalis isolates, as reported at 81.9%, 55% and 50% in isolates from South Africa, Cuba and United States, respectively.…”
Section: The Role Of Tlr3 During Trichomoniasismentioning
confidence: 99%
“…T. vaginalis may be infected with four types of dsRNA viruses (TVVs), belonging to the Totiviridae family 2 . Recently, Manny et al reported the presence of a novel TVV, namely TVV5 44 . T. vaginalis can harbour one or more types of TVVs 2 .…”
Section: The Role Of Pattern Recognition Receptors During Trichomoniasismentioning
confidence: 99%